Aspects of Fatal Burn Injury Cases Admitted to Al–Sadiq Teaching Hospital, Babylon Province/Iraq During 2020 (Medico Legal Update, 2020)
Background: Burns death both intentional and non-intentional considered among the most disastrousoutcome of burn injuries.Objectives: To measure the case fatality rate in hospitalized burn patients and to investigate in-hospitalmortality among burn injury cases who were admitted to Al–Sadiq Teaching Hospitalburn center from thefirst of January to the end of June, 2020.Methodology: This is an observational descriptive case series study conducted on all cases who died fromburn injury among patients who were admitted to the biggest teaching hospital in Babylon Province – Iraq.Data were collected from patients themselves or their companions and from patients’ hospital records, usinga pretested questionnaire designed for collection the requested information.Results: The mean age ± SD (Standard Deviation) of burn death victims were 24.5±17.66 years. Youngage group (15-24 years) represents the highest proportion (50%). Male to female ratio was 1:2.25. The casefatality rate was 26.6%(32/120). The majority of cases were from rural areas, 67% of suicidal burn deathshad more than 50% of burnt total body surface area. Intentional burn deaths victims had significantly severeburns (third degree burn and high-burnt surface area) as compared to accidental burn deaths. There was astatistically significant difference as regards the mode of burns between the intentional and accidental burndeaths, all intentional deaths were burnt with flame.Conclusions: The case fatality rate of burn injuries was high, females outnumbered males, and suicidal burndeaths were significantly associated with severe burn as compared to the accidental ones.